The WTO Trade Effect - CHANG, Pao Li (Institutional Knowledge at Singapore Management University, 2007)
Rose (2004) showed that the WTO or its predecessor, the GATT, did not promote trade, based on conventional econometric analysis of gravity-type equations of trade. We argue that conclusions regarding the GATT/WTO trade effect based on gravity-type equations are arbitrary and subject to parametric misspecifications. We propose using nonparametric matching methods to estimate the 'treatment effect' of GATT/WTO membership, and permutation-based inferential procedures for assessing statistical significance of the estimated effects. A sensitivity analysis following Rosenbaum (2002) is then used to evaluate the sensitivity of our estimation results to potential selection biases. Contrary to Rose (2004), we find the effect of GATT/WTO membership economically and statistically significant, and far greater than that of the Generalized System of Preferences (GSP).